1999
DOI: 10.1155/1999/183697
|View full text |Cite
|
Sign up to set email alerts
|

Management of Irritable Bowel Syndrome: Novel Approaches to the Pharmacology of Gut Motility

Abstract: Although it is unclear to what extent irritable bowel syndrome (IBS) symptoms represent a normal perception of abnormal function or an abnormal perception of normal function, many believe that IBS constitutes the clinical expression of an underlying motility disorder, affecting primarily the mid- and lower gut. Indeed, transit and contractile abnormalities have been demonstrated with sophisticated techniques in a subset of patients with IBS. As a consequence, drugs affecting gastrointestinal (GI) motility have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 102 publications
0
45
0
Order By: Relevance
“…As observed in vitro, experiments with the CCK1 receptor antagonist loxiglumide indicate that CCK affects human colonic motility in vivo. Indeed, this compound accelerates colonic transit in normal volunteers (313,438,449,538). Moreover, demonstration that small intestinal motility is in part mediated by CCK1R-induced signaling was recently supported by significantly lower transit rates in CCK1R null mice (553).…”
Section: Bowelmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in vitro, experiments with the CCK1 receptor antagonist loxiglumide indicate that CCK affects human colonic motility in vivo. Indeed, this compound accelerates colonic transit in normal volunteers (313,438,449,538). Moreover, demonstration that small intestinal motility is in part mediated by CCK1R-induced signaling was recently supported by significantly lower transit rates in CCK1R null mice (553).…”
Section: Bowelmentioning
confidence: 99%
“…Increased colonic response to CCK in vivo and in vitro has been observed (92). On the other hand, CCK1R antagonists have been evaluated clinically to stimulate transit and treat IBS (438,538). Loxiglumide caused significant improvement of symptoms in IBS while, in contrast to previous studies, dexloxiglumide was very recently reported to delay transit in the ascending colon in patients with constipation-predominant IBS (76, 104, 109).…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…14 Scarpignato et al used octreotide in small pulse doses in patients with irritable bowel syndrome and noticed that it accelerated intestinal transit. 15 Cullen et al used octreotide in postoperative ileus and showed that octreotide has a dose dependent action on colonic motility; used in low doses it acted as a prokinetic agent and resulted in patients having a bowel movement earlier. 16 We have used octreotide during colonic motility studies in seven patients who had no response to a standard dose of bisacodyl.…”
Section: Introductionmentioning
confidence: 99%
“…Besides decreasing colonic sensitivity to distension, these drugs prolong colonic transit and are particularly useful in diarrhea-predominant IBS (29). A 5-HT 3 receptor antagonist, alosetron, delays colonic transit in patients with IBS (2).…”
mentioning
confidence: 99%